Triphenylamine-benzimidazole derivatives : synthesis, excited-state characterization and DFT studies - Pina, J. (2013)
The synthesis and comprehensive characterization of the excited states of four novel triphenylamine-benzimidazole derivatives has been undertaken in solution (ethanol and methylcyclohexane) at room temperature. This includes the determination of the absorption, fluorescence and triplet-triplet absorption spectra, together with quantum yields of fluorescence, internal conversion, intersystem crossing and singlet oxygen. From the overall data the radiative and radiationless rate constants could be obtained and it is shown that the compounds are highly emissive with the radiative decay dominating, with more than 70% of the quanta loss through this deactivation channel. The basic structure of the triphenylamine-benzimidazole derivatives (1a) was modified at position 5 of the heterocyclic moiety with electron donating (OH (1b), OCH3 (1c)) or electron withdrawing groups (CN, (1d)). It was found that the photophysical properties remain basically unchanged with the different substitutions although a marked Stokes Shift was observed with 1d. The presence and nature of a charge transfer transition is discussed with the help of theoretical (DFT and TDFT) data. All compounds displayed exceptionally high thermal stability (between 399-454 ºC) as seen by thermogravimetric analysis.